1985
DOI: 10.2190/2uec-5ady-gjmb-4j6g
|View full text |Cite
|
Sign up to set email alerts
|

Single and Multiple Patterns of Adolescent Substance Use: Longitudinal Comparisons of Four Ethnic Groups

Abstract: Patterns of drug use for 847 adolescents from four different ethnic backgrounds were examined over a five-year period. Eight distinct patterns of use were identified. In addition to a nonuser group, only one large single substance use group emerged; that for alcohol use. Almost 60 percent of the participants were multiple users of two or more types of substances. Black students had consistently the highest frequency of single-cigarette smokers and the highest frequency of multiple use of alcohol-cigarette-cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0
2

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 15 publications
3
17
0
2
Order By: Relevance
“…These findings are supported by numerous studies conducted on the drug use behavior of non-Hispanic youth as well as by the few studies which have investigated the patterns of illicit and licit drug use of Hispanic individuals. 32 In line with the findings of other researchers are the results which indicate that youth of Mexican-American origin appear to use licit and illicit drugs at a higher rate than other Hispanic youth, except for Puerto Rican youth. 4,33 The findings from this research have consistently indicated that Mexican-American individuals use and abuse licit and illicit drugs at a higher rate than Cubans and South and Central American individuals.…”
Section: Discussion and Recommendationssupporting
confidence: 84%
“…These findings are supported by numerous studies conducted on the drug use behavior of non-Hispanic youth as well as by the few studies which have investigated the patterns of illicit and licit drug use of Hispanic individuals. 32 In line with the findings of other researchers are the results which indicate that youth of Mexican-American origin appear to use licit and illicit drugs at a higher rate than other Hispanic youth, except for Puerto Rican youth. 4,33 The findings from this research have consistently indicated that Mexican-American individuals use and abuse licit and illicit drugs at a higher rate than Cubans and South and Central American individuals.…”
Section: Discussion and Recommendationssupporting
confidence: 84%
“…In prospective studies of adolescents and young adults, the onset of substance use is most often associated with age, often beginning in adolescence and peaking in emerging adulthood (Chen and Jacobson, 2012; Clark et al, 2013; Maddahian et al, 1985). Drawing on data from the Monitoring the Future Study, Kroutil et al (2010) observed that lifetime prevalence use of alcohol and marijuana increased with age.…”
Section: Introductionmentioning
confidence: 99%
“…There is a tendency to view Asian Pacific Islanders (APIs) in the United States as having low risk for substance use (Maddahian et al, 1985;Bachman et al, 1991). The perception of APIs as a "model minority" bolsters this perception (Zane & Kim, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…According to this belief, APIs represent a socioeconomically privileged minority group having only modest risk for adverse psychosocial and health outcomes such as substance use (Chen & Hawks, 1995). Epidemiological data from national samples have suggested that APIs experience the lowest substance use rates compared with African Americans, Latinos, and White Americans (Bachman et al, 1991;Maddahian et al, 1985;SAMHSA, 2002). However, some studies challenge this categorical view with findings that show high substance use among certain API demographic subgroups (Ellickson & Morton, 1999;Nemoto et al, 2002;Oetting et al, 2000;Price et al, 2002).…”
Section: Introductionmentioning
confidence: 99%